Missing sports talent: Bias (RAE) in youth sports` athlete selection - Ramos, N. C.; Venturini, A. C. R.; dos Santos, A. P.; Machado, D. R. L. (Research Quarterly for Exercise and Sport, 2018)
Background/Purpose: Relative age effect (RAE) is a bias in the selection of athletes in youth sports, where athletes born in the early months of the year are perceived to be more talented and are selected purely because of maturity-related advantages in body size, strength, speed and endurance (Braun & Clarke, 2006). This temporary advantageous condition may increase the risk of missing potential sports talents (Deprez et al., 2013). While there is evidence that RAE exists, it is still unknown if these physical abilities are decisive in choosing the best athletes and what is the impact of RAE on technical skills and physical abilities required for competition. The purpose of this study was to identify RAE`s occurrence, RAE`s association with players` technical skills, and how RAE affects the performance of specific motor tasks for game performance. Method: Participants were 54 young elite soccer players from Botafogo F.C., Brazil, in the base teams under-15 (n = 21), under-17 (n = 19) and under-20 (n = 14) age groups. Athletes were grouped according to their birth months into four birth quarters (BQs). Athletes` technical skills were determined by their coaches, who ranked players` Technical Rankings (TR), from best to worse, one time together (General TR) and another according to their field position (Position TR). Physical Ability (PA) was determined by five performance tests: speed (30m-run in m/min); agility (t-test in sec); power (six bounding jumps in m); average, minimum, maximum and relative (fatigue index/kg) power (RAST anaerobic test in watts); and maximum oxygen uptake (Lèger multi-stage test in VO2max). Analysis/Results: Frequency analysis revealed players born in the first half of the year were selected the most (U-15 = 77.1%; U-17 = 65.4%; U-20 = 50.0%). The association between BQs and skills (TR) was tested by Spearman`s rank correlation coefficient (Spearman`s Rho) and ranged from low to moderate (0.22 to 0.53) in general ranking and (0.04 to 0.25) in position ranking. ANOVA (one-way) was used to indicate the differences between BQs PA. When comparing age-group categories, the performance of the PA tests did not show statistical differences in the majority of the comparisons. However, U-20 performed better on Average Power (F = 4.644, p = .006), Maximum Power (F = 4.460, p = .008) and Relative Power (F = 6.143; p = .008). U-17 performed the shortest times on Speed and Agility tests in the comparisons of all BQs. Conclusions: Findings provided strong evidence of RAE in U-15 with diminished prevalence in older teams U-17 and U-20. It was not possible to conclude that RAE can affect the performance of physical abilities. It appears that RAE has no effect on the technical skills of young players, but it can be determinant in the best performance of motor tasks, especially when age grouping or specific physical abilities are required for a given task. The low association between BQs and TRs reinforces that the selection of athletes for a team is independent of their technical skills, increasing the risk of misguided technical selection, especially in the younger categories. Contact: niloramos@hotmail.com